EVENT MANAGEMENT IN THE FUNCTION OF CULTURAL TOURISM DEVELOPMENT - Todorov, Predrag; Borković, Milana; Tošić, Teodora (The Business of Tourism, 2023)
Abstract: Tourism is one of the world-leading businesses that represent a major generator of socio-economic development in many countries, even underdeveloped ones. The events are activities that belong to a group of formed activities, which should be a part of every tourist destination that aims to have successfully developed tourism. Trips that are primarily focused on visiting certain manifestations are portrayed as tourism of manifestations or event tourism. The manifestations are spatio-temporal phenomena, each unique due to the mutual interaction of place, domiciled inhabitants, tourists, and the managing system, including program and concept. The events that bring tourists to a certain destination can be related to culture, art, sports, entertainment, business, and even politics. This paper aims to emphasize the importance of ethnographic manifestations in Serbia as indeed a priceless intangible cultural heritage that has a huge influence and significance on the development of the local environment, as well as on the positioning of the entire country as a manifestational tourist destination with over 1500 events per year. Keywords: event management, manifestations, cultural tourism, intangible cultural heritage.